Nanopartículas de TiO2:WO3 e ZnO obtidas pela utilização de moinho vibratório: caracterização e propriedades fotocatalíticas - Storion, Ana Gabriela (2018)
Advanced Oxidation Processes (AOP) are widely studied as alternative water treatments. Heterogeneous photocatalysis (a method of POA) consists in the activation of a semiconductor by radiation, generating oxidizing and reducing sites, which will mineralize the pollutants. The surface area of ​​a photocatalyst is a very important property, since the processes will activate and occur on its surface, which makes it necessary to obtain powders on a nanometric scale. The present work aimed to study the application of High Energy Ball Milling performed in a SPEX 8000 Mixer/Mill, with ball to powder weight ratio of 5:1, to obtain nanostructured powders of TiO2:WO3 and ZnO, under different compositions and milling times. The photocatalytic activity was evaluated through decomposition of Rhodamine B (RhB). The powders were characterized by B.E.T., Helium pycnometry, X ray diffraction, DSC/TG and FTIR and submitted to the milling process. For the TiO2:WO3 system, different bulk compositions were considered (0:100, 30:70, 50:50, 70:30 and 100: 0), each one milled for 2, 4, 6 and 8 hours. For ZnO, milling times of 1, 2, 3, 4 and 5 hours were carried out. After grinding, acid leaching was performed to remove the iron from the grinding medium, using 6.5 M ​​hydrochloric acid and 0.5 M oxalic acid. The powders were deagglomerated and characterized by X-ray diffraction, scanning electron microscopy and X-ray fluorescence. Finally, the photocatalytic tests were carried out in a photochemical reactor with incidence of ultraviolet radiation. The results showed that High Energy Milling using SPEX 8000 mill presents potential of obtaining powders in nanometric scale. For zinc oxide, 1 hour of milling was enough to achieve nanometric scales, as well as 2 hours of milling for the TiO2:WO3 system. Through chemical analysis, it was observed that the leaching performed was not efficient in the iron removal. For the TiO2:WO3 system, both leaching decreased the iron percentage, but the hydrochloric acid led to the formation of larger agglomerates and particles of differentiated morphology. For ZnO, the use of oxalic acid led to the formation of zinc oxalate which, in turn, provided particle growth to micrometric scale. The processed materials via MAE presented lower photocatalytic activity for the degradation of RhB using UV radiation. This behavior may be related to the structural transformations occurred during processing, iron incorporation in the materials structure, appearance of crystalline imperfections and an elevation in the recombination rate of the photogenerated pairs.